Different Fecal Microbiota in Hirschsprung's Patients With and Without Associated Enterocolitis - Arnaud, Alexis P.; Cousin, Ianis; Schmitt, Françoise; Petit, Thierry; Parmentier, Benoit; Levard, Guillaume; Podevin, Guillaume; Guinot, Audrey; DeNapoli, Stéphan; Hervieux, Erik; Flaum, Valérie; De Vries, Philine; et al. (Frontiers in Microbiology, 2022)
Background and objectives: Hirschsprung’s disease (HD) patients are at risk of developing Hirschsprung’s disease associated enterocolitis (HAEC), especially in the first two years of life. The pathophysiology of this inflammatory disease remains unclear and intestinal dysbiosis has been proposed in the last decade. The primary objective of this study was to evaluate in a large cohort if HAEC was associated with alterations of fecal bacterial composition compared to HD without HAEC in different age classes. Methods: We analyzed the fecal microbiota structure of 103 HD patients from 3 months to 16 years of age, all of whom had completed definitive surgery for rectosigmoid HD. 16S rRNA gene sequencing allowed us to compare the microbiota composition between HD patients with or without HAEC in different age classes (0-2 years, 2-6 years, 6-12 years, 12-16 years). Results: Richness and diversity increased with age class but did not differ between HD and HAEC patients, irrespective of the age class. Relative abundance of Actinobacteria was lower in HAEC compared to HD patients under 2 years of age (-66%, P=0.045). Multivariate analysis by linear models (MaAsLin) considering sex, medications, birth mode, breast-feeding and the Bristol stool scale as well as surgery parameters highlighted Flavonifractor plautii, Ruminococcus gnavus group and Eggerthella lenta as positively associated with HAEC in the 0-2 years age group. Conclusion: HAEC was associated with features of intestinal dysbiosis in infants (0-2 years) but not in older patients. This could explain the highest rate of HAEC in this age group.